NKG2D- and T-cell receptor-dependent lysis of malignant glioma cell lines by human γδ T cells: Modulation by temozolomide and A disintegrin and metalloproteases 10 and 17 inhibitors. (2nd April 2016) - Chitadze, Guranda; Lettau, Marcus; Luecke, Stefanie; Wang, Ting; Janssen, Ottmar; Fürst, Daniel; Mytilineos, Joannis; Wesch, Daniela; Oberg, Hans-Heinrich; Held-Feindt, Janka; Kabelitz, Dieter
ABSTRACT: The interaction of the MHC class I-related chain molecules A and B (MICA and MICB) and UL-16 binding protein (ULBP) family members expressed on tumor cells with the corresponding NKG2D receptor triggers cytotoxic effector functions in NK cells and γδ T cells. However, as a mechanism of tumor immune escape, NKG2D ligands (NKG2DLs) can be released from the cell surface. In this study, we investigated the NKG2DL system in different human glioblastoma (GBM) cell lines, the most lethal brain tumor in adults. Flow cytometric analysis and ELISA revealed that despite the expression of various NKG2DLs only ULBP2 is released as a soluble protein via the proteolytic activity of "a disintegrin and metalloproteases" (ADAM) 10 and 17. Moreover, we report that temozolomide (TMZ), a chemotherapeutic agent in clinical use for the treatment of GBM, increases the cell surface expression of NKG2DLs and sensitizes GBM cells to γδ T cell-mediated lysis. Both NKG2D and the T-cell receptor (TCR) are involved. The cytotoxic activity of γδ T cells toward GBM cells is strongly enhanced in a TCR-dependent manner by stimulation with pyrophosphate antigens. These data clearly demonstrate the complexity of mechanisms regulating NKG2DL expression in GBM cells and further show that treatment with TMZ can increase the immunogenicity of GBM. Thus, TMZ might enhance the potential of the adoptive transfer of ex vivo expanded γδ T cells for the treatment of malignant glioblastoma.